The concept “plastic culture” in the context of acting - N. Ihnatieva (Культура України)
A person exists in a certain cultural environment and is always adapting to it. The human need for movement and self-expression contributes to the development of sports, theater, dance, and pantomime. Sport allows you to develop and demonstrate the physical capabilities of a person. Dance, pantomime, and acting create artistic images that reflect the character’s nature, feelings, emotions, spiritual values, and attitude to certain personal events as well as social life.